Effect of Fe and Ti doping on Mn site of La0.7Ba0.3Mn0.85Fe0.15-xTixO3 as electromagnetic wave absorbing material - Ikhsan, Fauzul; Kurniawan, Budhy; Razaq, Dhawud Sabilur; Munazat, Dicky Rezky; Putri, Witha. B. K. (AIP conference proceedings, 2023)
Lanthanum manganite-based perovskite has been the subject of numerous research to this day. In this paper, we synthesize La0.7Ba0.3MnO3 (LBMO) and substitute La and Mn ions withother ions. Substitution of Ba ions at the La site produces electromagnetic wave-absorbing properties. Further, at the Mn site, variations of Fe and Ti doping are added into the LBMO with compositions La0.7Ba0.3Mn0.85Fe0.15-xTixO3 (x=0; 0.15). The synthesis of LBMO using the sol-gelmethod resulted in a single-phase Rhombohedral crystal structure with Space Group R-3c. The increase in Ti value in LBMFTO causes a decrease in the crystal volume. In addition, at a certain diffraction angle, the shifting and widening of the diffraction patterns are noticeable. The combination of doping resulted in an increased absorbance value of LBMO. The test results showthat the combination of Fe and Ti at x=0.05 produces the largest wave absorption value. We investigate the correlation between changes in doping variations and in wave absorption values.